Algebraic competences and emotional intelligence of first year Bachelor of Science in Mathematics and Science Education students at the Copperbelt University in Zambia - Allan Musonda (Universidad de Deusto, 2017)
This study examined the relationship between algebraic competences and emotional intelligence of first year Bachelor of Science in mathematics and science education students at Copperbelt University in Zambia. All (143) first year Bachelor of Science in mathematics and science education students, in 2016, were purposively selected for the study. The study was motivated by evidence that students generally do not perform well in their first year university mathematics examinations despite the students having very good university entry grades in secondary school mathematics. This poor academic performance may be due to many factors. However, this study identified and focused on emotional intelligence as one such factor. Emotional intelligence is defined as the ability to identify, assess and manage the emotions of one's self, of others and of groups. It is argued that emotional intelligence represents an ability to reason with emotions and to use emotions to facilitate thought. On the other hand, Algebra was chosen as the focus of the study because of its centrality to the whole of first year university mathematics content. Algebra is found in all branches of mathematics directly or indirectly. Therefore, the study explored the algebraic competences of the first year students and examined possible relationships with their emotional intelligence. Emotional intelligence was measured using the Schutte Self-Report Emotional Intelligence Test (SSEIT), and algebraic competences were measured through a Grade 12 level algebra achievement test and a university level algebra achievement test constructed by the researcher. Data were analysed using non-parametric statistical techniques: Spearman's Rank Order Correlation (rho) and the Mann-Whitney U Test. Results showed that there is a significant positive correlation between Grade 12 level and first year university level algebraic competences. Results also showed that there is no significant relationship between students' algebraic competences and their emotional intelligence. Furthermore, the study reviewed that female students have higher levels of emotional intelligence than their male counterparts. First published online: 30 November 2017